Vitamin D and immunity: reality or phantasy? - Hamid Jan Jan Mohamed (World Nutrition Journal, 2022)
Vitamin D has been attracting a lot of attention from researchers, pharmaceutical industries and public mainly because of its potential extra-skeletal effects in health and in various diseases such as diabetes, cardiovascular diseases, cancer and autoimmune diseases. Historically, vitamin D was associated with diseases such as rickets in children and osteoporosis is adults. However, during the COVID-19 pandemic, vitamin D gained a special focus related to its immune modulating ability